Spremljanje pritalne vegetacije gozdov v Sloveniji kaže na zmanjševanje števila rastlinskih vrst - Kutnar, Lado (Gozdarski vestnik, 2024)
The monitoring of the state and changes in ground vegetation in Slovenian forests are conducted within the framework of the international ICP Forests programme at two distinct levels: Level 1 and Level 2. At Level 2, which encompasses representative intensive forest monitoring plots (IM plots), the status of ground vegetation has been subjected to systematic monitoring since 2004. The fourth repetition of the survey, conducted in 2019/2020, revealed a decline in species richness in the herb layer. On average, the number of species declined by –7.1% in the larger vegetation sub-plots and by –11.2% in the smaller ones. Although the number of species has decreased in the majority of IM plots (most notably in lowland forests), species diversity has also increased in some plots, primarily as a result of large-scale disturbances. In the future, in the context of monitoring changes in the ground vegetation of forests, we will also pay more attention to the processes of thermophilisation, eutrophication and biotic homogenisation, which are already observed in the ground vegetation of Slovenian forests.
Keywords: ground vegetation monitoring; herb layer; intensive monitoring; intenzivni monitoring; large-scale disturbances; plant species richness; species diversity; spremljanje pritalne vegetacije; številčnost rastlinskih vrst; velikopovršinske motnje; vrstna pestrost; zeliščna plast